Non-fungible token: A systematic review and research agenda - Hong Bao; David Roubaud (Journal of Risk and Financial Management, 2022)
The popularity of the Non-Fungible Token (NFT) has risen rapidly since 2020, becoming one of the most popular applications in the Fintech field. However, there has so far been no attempt to perform a systematic review in this new area. Considering the items of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), this paper conducts a systematic review of the research work on NFT, published in journals indexed at the Web of Science and ScienceDirect until April 2022. The results reveal that there are 13 published articles in the targeted journals and they are mainly focused on the asset pricing area. The research gaps identified in the literature also can be the opportunity for future study. Thus, we lay down the research agenda for the future in several important but unanswered fields related to asset pricing, tokenomics, and risk and regulation.
Keywords: 650; non-fungible token; research agenda; systematic review